Bringing Technological Frames to Work: How Previous Experience with Social Media Shapes the Technology's Meaning in an Organization. (18th March 2015) - Treem, Jeffrey W.; Dailey, Stephanie L.; Pierce, Casey S.; Leonardi, Paul M.
<x xml:space="preserve">Abstract</x> This study examines the expectations that workers have regarding enterprise social media (ESM). Using interviews with 58 employees at an organization implementing an ESM platform, we compare workers' views of the technology with those of existing workplace communication technologies and publicly available social media. We find individuals' frames regarding expectations and assumptions of social media are established through activities outside work settings and influence employees' views about the usefulness of ESM. Differences in technological frames regarding ESM were related to workers' age and level of personal social media use, but in directions contrary to expectations expressed in the literature. Findings emphasize how interpretations of technology may shift over time and across contexts in unique ways for different individuals.